An Optimization-Based Reconfigurable Design for a 6-Bit 11-MHz Parallel Pipeline ADC with Double-Sampling S&H. (16th August 2012) - Carvajal, Wilmar; Van Noije, Wilhelmus
Abstract : This paper presents a 6 bit, 11 MS/s time-interleaved pipeline A/D converter design. The specification process, from block level to elementary circuits, is gradually covered to draw a design methodology. Both power consumption and mismatch between the parallel chain elements are intended to be reduced by using some techniques such as double and bottom-plate sampling, fully differential circuits, RSD digital correction, and geometric programming (GP) optimization of the elementary analog circuits (OTAs and comparators) design. Prelayout simulations of the complete ADC are presented to characterize the designed converter, which consumes 12 mW while sampling a 500 kHz input signal. Moreover, the block inside the ADC with the most stringent requirements in power, speed, and precision was sent to fabrication in a CMOS 0.35  μ m AMS technology, and some postlayout results are shown.